Genetics of Obesity in Consanguineous Populations: Toward Precision Medicine and the Discovery of Novel Obesity Genes. Issue 3 (21st February 2018) - Saeed, Sadia; Arslan, Muhammad; Froguel, Philippe
Abstract : Objective: Consanguinity has been instrumental in the elucidation of many Mendelian genetic diseases. Here, the unique advantage of consanguineous populations was considered in the quest for genes causing obesity. Methods: PubMed was searched for articles relevant to consanguinity and obesity published between 1995 and 2016. Some earlier articles of interest were also consulted. Results: Although obesity is the most heritable disorder, even in outbred populations, only 2% to 5% of severe obesity cases have so far been proven to be caused by single gene mutations. In some highly consanguineous populations, a remarkably higher proportion of obesity cases because of known and novel monogenic variants has been identified (up to 30%). Conclusions: Combining the power conferred by consanguinity with current large‐capacity sequencing techniques should bring new genetic factors and molecular mechanisms to the fore, unveiling a large part of the yet‐elusive neurohumoral circuitry involved in the regulation of energy homeostasis and appetite. Importantly, the undertaking of such initiatives is destined to unfold novel targets for the development of precision medicine relevant to different forms of obesity.